Percentage of students enrolled with disabilities in common or special classes exclusively in Brazil – 2015 to 2019 (Research, Society and Development, 2022)
The article aimed to survey the databases of the National Institute of Educational Studies and Research Anísio Teixeira (INEP) and the Directorate of Educational Statistics (DEED on enrollment of students with disabilities, pervasive developmental disorders or discharge). s skills in common or exclusive special classes in Brazil between the years 2015 to 2019. This survey showed that, The number of enrollments in special education reached 1.3 million in 2019, an increase of 34.4% compared to 2015, the percentage of students with disabilities, autism spectrum disorders or high abilities enrolled in regular classes has gradually increased for all stages of education, it was found that the percentage of enrollments of students included in regular classes increased gradually over the years In 2015, the percentage of students included was 88.4% and, in 2019, it rose to 92.8%, finally offering inclusive education for administrative dependence. It was observed that the state (96.7%) and municipal (95.9%) networks had the highest percentages of students. The data show that special education students are managing to reach universities, studies by the National Institute of Educational Studies and Research Anísio Teixeira (INEP) show that there is an increase in the enrollment of students with a disability in universities. Where, in the past, there were no students in ordinary classes in schools attending some kind of grade.